Implementasi Sintesis Suara Saron Menggunakan Petikan Senar Gitar Dengan Metode Pitch Shifting - Andreas Febrillianto Primawan; Yohannes Suyanto; Catur Atmaji (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2023)
Â Gamelan is traditional Indonesian musical instruments that is often used in traditional events and parties.The community's need for the gamelan has actually increased, but unfortunately the price of gamelan is very expensive and the gamelan itself is difficult to move from one place to another place. Besides that, the limited tones that can be played by gamelan reduce the level of public interest in playing this instrument. Current technological developments make it possible to perform voice synthesis with several methods. One method that can be used is pitch shifting.This study aims to generate a synthetic saron sound based on plucking a guitar string. Analysis of the saron sound signal in the frequency domain is carried out to obtain the semitone values needed in the synthesis process. Synthetic saron signal generation is done by calling synthetic saron sounds that are stored in soundfont form, with reference data in the form of high and low pitch obtained from the guitar input pitch detection. Onset detection of guitar strokes is used as the initial trigger for calling out synthetic saron tones. The test was carried out by looking for similarities between the sound data of the original saron and synthetic saron using the cross-correlation method. The test results obtained a similarity accuracy rate of 91.6%. On the results of testing the guitar strum signal with the generation output, the average delay time for each strum is 0.152 seconds. From the results obtained, the system is classified as fast and accurate enough to be implemented in everyday life.